r(2x+3)=0.5x+1

Simple and best practice solution for r(2x+3)=0.5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for r(2x+3)=0.5x+1 equation:


Simplifying
r(2x + 3) = 0.5x + 1

Reorder the terms:
r(3 + 2x) = 0.5x + 1
(3 * r + 2x * r) = 0.5x + 1
(3r + 2rx) = 0.5x + 1

Reorder the terms:
3r + 2rx = 1 + 0.5x

Solving
3r + 2rx = 1 + 0.5x

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Reorder the terms:
-1 + 3r + 2rx + -0.5x = 1 + 0.5x + -1 + -0.5x

Reorder the terms:
-1 + 3r + 2rx + -0.5x = 1 + -1 + 0.5x + -0.5x

Combine like terms: 1 + -1 = 0
-1 + 3r + 2rx + -0.5x = 0 + 0.5x + -0.5x
-1 + 3r + 2rx + -0.5x = 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
-1 + 3r + 2rx + -0.5x = 0.0

The solution to this equation could not be determined.

See similar equations:

| b^2=-2+3b | | 20x+12y=344 | | 2(5z-1)-5(z+9)=2(z+1) | | 18-3x=2+2x | | 9n^2=-1 | | 5(3/2)+3(4/2)= | | 41+a=10 | | 2xy-3y+6=0 | | 3x-5=24+7 | | (3x-18)=105+99 | | 5.4+-9.7= | | 2/3x-1/2=3/4 | | 29n=-377 | | 2(x+3)=4*-3 | | (2x-4)2=36 | | 4(6x-31)=5-4(x+3) | | 7(4x+8)-6=-106 | | 3v^2+12v=-8 | | 7x-4=-2x+2+9x-5 | | 9(x+1)=25+6 | | -2(2-x)=-8+6x | | 11+2n=9 | | -7(1x-6)=-14 | | 57=5x-3 | | -3(5m+4)-3(m-7)= | | y-12=89 | | 5x^2+11xy+2y^2=0 | | mx=-nx+p | | 9x-15=9(x-13) | | 38=8+6(y+2) | | 136=-17b | | -27.083x-11.246-16.819= |

Equations solver categories